A Comparative Study in Entrepreneurship Between South Korea and Colombia - Rojo Gutiérrez, Dr. Marco Antonio; Carlos Olaya Molano, Mr. Juan; Padilla Oviedo, Dr. Andres; Ramon Ramirez, Dr. Juan (IJRDO - Journal of Social Science and Humanities Research, 2017)
Entrepreneurship is one of the factors that contribute to economic growth. The present study compares the entrepreneurship between South Korea and Colombia; it identifies best practices that increase entrepreneurship as an ecosystem conditions for both countries. Also, this study provides evidence on how implementing reforms improve entrepreneurship by reducing the processes and number of days required to attain goals. The use of new technologies and organizational innovation allowed improving the processes. Furthermore, creating universal formats reduced the costs throughout the new production unit was established. In addition, transparency, access to information, work regulation, and the government role in creating new companies in respect to demand are topics of a pending agenda in favor of entrepreneurship for both countries.